Pengaruh Akuntabilitas, Transparansi Dan Partisipasi Masyarakat Terhadap Pengelolaan Apbdes Desa Sidokare Kecamatan Rejoso Kabupaten Nganjuk Tahun 2022 - Utari, Chintya Wandira; Nawangsari, Ertien Rining (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
This study aims to determine the influence of accountability, transparency, and community participation on the management of Village Budget Allocation (APBDes) in Sidokare Village, Rejoso District, Nganjuk Regency, in 2022. The research method used is quantitative with a correlation approach. Data was collected through a questionnaire that was tested for validity and reliability. The research sample consisted of 95 respondents selected using purposive sampling technique. Data analysis was conducted using multiple linear regression. The results of the study show that accountability, transparency, and community participation partially and simultaneously have a positive and significant influence on the management of APBDes in Sidokare Village. The variable of community participation has a dominant influence on APBDes management. The results of the determination test show that 89% of the variations in APBDes management can be explained by the variables of accountability, transparency, and community participation. This study concludes the importance of enhancing accountability, transparency, and community participation in APBDes management to achieve better management in Sidokare Village.